Dietary Laws in Medieval Christian-Jewish Polemics: A Survey - Resnick, Irven (Studies in Christian-Jewish Relations, 2011)
In the religious debate between Jews and Christians, the biblical dietary laws come to illustrate important assumptions concerning the “other.” Early medieval Christians asserted that Christians were not bound by the dietary laws and tended to explicate them allegorically or figuratively. Although the biblical dietary laws prohibit many foods to Jews, as pork became a more important part of the medieval diet, the prohibition against swine’s flesh became central to the debate. Christians will assert not only that the consumption of pork proclaims a correct messianic theology, but also that the Lord, like a good physician, ordained a special diet for the Jews because they—and not Christians—have a corrupt bodily nature that is subject to deleterious influences from pork that incline Jews to gluttony and wantonness. Therefore, when a Jew converted to Christianity, the consumption of pork became a sign of his transfer from one religious community to another, as well as a sign of a physical, intellectual, and moral transformation.